Poly(dihydroxybenzoquinone): its high-density and robust charge storage capability in rechargeable acidic polymer–air batteries. Issue 29 (25th March 2020) - Oka, Kouki; Furukawa, Shuhei; Murao, Saki; Oka, Tatsuya; Nishide, Hiroyuki; Oyaizu, Kenichi
Abstract : A rechargeable acidic polymer–air battery was firstly fabricated, which exhibited a long-lifetime of >500 cycles and high rate capabilities. Abstract : A rechargeable acidic polymer–air battery was firstly fabricated with poly(2, 5-dihydroxy-1, 4-benzoquinone-3, 6-methylene) (PDBM) as the anode, the conventional Pt/C cathode catalyst, and acidic aqueous electrolyte (pH 1). This battery yielded a high discharging capacity of 349 mA h gpolymer −1 with a long-lifetime of >500 cycles and high rate capabilities (up to 10C).